2021
DOI: 10.3233/jad-210699
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Cognitive Decline and Prevalence of Mild Cognitive Impairment in the Iwaki Health Promotion Project

Abstract: Background: The Iwaki Health Promotion Project (IHPP) is a community-based study for the prevention of lifestyle-related diseases and improvement of quality of life. Objective: Between 2014 and 2017, a total of 4,442 Iwaki town residents from 19 to 93 years of age participated in annual surveys to clarify the natural course of age-related cognitive decline and mild cognitive impairment (MCI). Methods: Modified OLD and SED-11Q questionnaires, MMSE, Logical Memory II, educational history, and APOE genotypes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…Consistent with a Brazilian community sample, education also did not have an important effect on memory registration [38]. However, overall MMSE scores are highly dependent on educational level: low education levels may affect the understanding of MMSE tests [39][40][41]. Furthermore, with increasing educational duration, the levels of MMSE scores increase.…”
Section: Discussionsupporting
confidence: 66%
“…Consistent with a Brazilian community sample, education also did not have an important effect on memory registration [38]. However, overall MMSE scores are highly dependent on educational level: low education levels may affect the understanding of MMSE tests [39][40][41]. Furthermore, with increasing educational duration, the levels of MMSE scores increase.…”
Section: Discussionsupporting
confidence: 66%
“…Studies eligible to be included in this review were required to meet the following criteria: Population: Adults 50 years or older with Mild Cognitive Impairment (at least 50% of the sample aged ≥ 50 years). In a study by Nakahata et al, 18 age and education related cognitive decline began and advanced from age 55 years. A younger age (50 years or more) was used to ensure all relevant articles available for people aging with Mild Cognitive Impairment were included.…”
Section: Methodsmentioning
confidence: 96%
“…16 Multiple community prevalence studies of cognitive impairment include patients starting at age 55, [17][18][19] and prior study has suggested age-related cognitive decline begins and advances after age 55. 20 Patient demographics, comorbidities, CI diagnoses, use of OAB medication and/or onabotulinum toxin, and SNM procedure details were collected. A patient was categorized as having cognitive impairment if they had any diagnosis code for dementia or MCI, or if the patient had an active prescription for a medication that is primarily used to treat dementia (donepezil, galantamine, rivastigmine, or memantine).…”
Section: Methodsmentioning
confidence: 99%
“…Although age 60 years or more is considered by the World Health Organization as “older,” 15 we used age 55 years as the lower limit for inclusion criteria to capture patients who may have earlier onset cognitive impairment and/or received a diagnosis during their follow‐up period after implantation 16 . Multiple community prevalence studies of cognitive impairment include patients starting at age 55, 17–19 and prior study has suggested age‐related cognitive decline begins and advances after age 55 20 …”
Section: Methodsmentioning
confidence: 99%